2020
DOI: 10.1001/jamanetworkopen.2020.0341
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patient-Physician Concordance in the Understanding of Chemotherapy Treatment Plans Among Patients With Cancer

Abstract: IMPORTANCEThe treatment plans of patients with cancer involve multiple modalities that oncologists need to explain to patients. One such modality is chemotherapy, in which information about the goals, duration, and expected complications of therapy are considered fundamental to achieving optimal patient understanding. Therefore, effective communication between patients and their treating physicians is important to ensure patient adherence to treatment and achieve better outcomes. OBJECTIVETo investigate the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…We found that many patients in both components of our study felt they understood their MTB treatment recommendations, which is contrary to findings in literature [34,[50][51][52]. Patients in our study reported that their treatment recommendations from MTB were clear and useful, and that they liked being included in the decision-making process.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that many patients in both components of our study felt they understood their MTB treatment recommendations, which is contrary to findings in literature [34,[50][51][52]. Patients in our study reported that their treatment recommendations from MTB were clear and useful, and that they liked being included in the decision-making process.…”
Section: Discussioncontrasting
confidence: 99%
“…Although patients reported that they discussed their treatment goals in 82% of the cases with their oncologists and oncologists in 91% of the cases with the patient, we found overall low concordances between patients' and oncologists' goals: between 24% for 'decrease in tumor growth' and 37% for 'quality of life.' A recent study by Almalki et al 26 found that only 13.7% of patients had full concordance with their physicians regarding the aspects of their treatment plans. However, this study consisted of a heterogeneous cancer population.…”
Section: Discussionmentioning
confidence: 98%
“…The concept of concordance underpins patient centred care—although the descriptive term receives scant reference in studies. In the healthcare setting, concordance is a mutual understanding or agreement concerning treatment between physician and patient [ 1 , 102 104 ]. A lack of concordance is shown to result in expectations that differed between patient and physician.…”
Section: Concordancementioning
confidence: 99%
“…By way of example, in a comprehensive study concerning oral cancer adherence in older adults the term concordance receives no reference and is seen in only one of eighty-four citations [ 31 ]. In a report into chemotherapy treatment plans, only a relatively low number of patients were in full concordance with their physician regarding chemotherapy treatment plans [ 102 ]. This was due to a ‘suboptimal understanding of aspects of their chemotherapy treatment plans’ [ 102 , p.11].…”
Section: Concordancementioning
confidence: 99%
See 1 more Smart Citation